UPAYA MEWUJUDKAN KELUARGA SAKINAH DI KALANGAN TNI DITINJAU DARI HUKUM ISLAM (Studi Kasus Keluarga Batalyon Infanteri 642/Kapuas Komisariat Kompi Senapan A Nanga Pinoh) - Mardhiyah, Umroatun; Hasan, Muhammad; Ardiansyah, Ardiansyah (Al-Usroh, 2022)
The purpose of this research is to determine: 1) Efforts to create a harmonious family among the TNI families in the Infantry Battalion 642/Kapuas Komisariat Rifle Company A Nanga Pinoh. 2) Efforts to realize religious observance among TNI families in the 642nd Infantry Battalion/Kapuas Commissariat of A Nanga Pinoh Rifle Company. 3) Efforts to create psychological peace among the TNI families in the 642nd Infantry Battalion/Kapuas Commissariat of A Nanga Pinoh Rifle Company. 4) Efforts to realize the economy among the TNI families in the Infantry Battalion 642/Kapuas Commissariat of A Nanga Pinoh Rifle Company. This study uses a qualitative writing method in the form of field writing and an empirical approach. The data source in this study used primary data in the form of interviews with husband and wife couples in the Infantry Battalion 642/Kapuas Komisariat Rifle Company A Nanga Pinoh. Interviews, documentation, and observation are some of the data collection approaches used. Technical analysis of the data the author began to perform data reduction, data presentation and conclusions. Then the technique of checking the validity of the data by using source triangulation. The results of this study indicate that: 1) The efforts made by the TNI family in realizing a harmonious family are always keeping promises to their partners, trying to always prioritize honesty with their partners, trying to be open to each other and trying to always be committed to their partners. 2) The efforts made by the TNI family in realizing religious observance are performing the five daily prayers, fasting and paying zakat. 3) The efforts made by the TNI family in realizing psychological peace are conducting positive family dialogues in daily life, avoiding violence in the family and maintaining family communication. 4) The efforts made by the TNI family in realizing the family economy are being able to manage family finances, have a simple lifestyle, have a side business and invest.